Identification, characterization and field testing of Brassica napus mutants producing high‐oleic oils. (28th January 2019) - Bai, Shuangyi; Engelen, Steven; Denolf, Peter; Wallis, James G.; Lynch, Katherine; Bengtsson, Jesse D.; Van Thournout, Michel; Haesendonckx, Boris; Browse, John
Summary: Producing healthy, high‐oleic oils and eliminating trans ‐fatty acids from foods are two goals that can be addressed by reducing activity of the oleate desaturase, FAD2, in oilseeds. However, it is essential to understand the consequences of reducing FAD2 activity on the metabolism, cell biology and physiology of oilseed crop plants. Here, we translate knowledge from studies of fad2 mutants in Arabidopsis ( Arabidopsis thaliana ) to investigate the limits of non‐GMO approaches to maximize oleic acid in the seed oil of canola ( Brassica napus ), a species that expresses three active FAD2 isozymes. A series of hypomorphic and null mutations in the FAD2.A5 isoform were characterized in yeast ( Saccharomyes cerevisiae ). Then, four of these were combined with null mutations in the other two isozymes, FAD2.C5 and FAD2.C1. The resulting mutant lines contained 71–87% oleic acid in their seed oil, compared with 62% in wild‐type controls. All the mutant lines grew well in a greenhouse, but in field experiments we observed a clear demarcation in plant performance. Mutant lines containing less than 80% oleate in the seed oil were indistinguishable from wild‐type controls in growth parameters and seed oil content. By contrast, lines with more than 80% oleate in the seed oil had significantly lower seedling establishment and vigor, delayed flowering and reduced plant height at maturity. These lines also had 7–11% reductions in seed oil content. Our results extend understanding of the B. napus FAD2 isozymes and define the practical limit to increasing oil oleate content in this crop species. Significance statement: An analysis of three FAD2 isozymes from canola and the characterization of multiple‐mutant lines define a limit to the production of high‐oleic oil in this crop.